Information Asymmetry, R&D, and Insider Gains - Aboody, David; Lev, Baruch (Journal of Finance, 2000)
Although researchers have documented gains from insider trading, the sources of private information leading to information asymmetry and insider gains have not been comprehensively investigated. We focus on research and development (R&D)—an increasingly important yet poorly disclosed productive input—as a potential source of insider gains. Our findings, for the period from 1985 to 1997 indicate that insider gains in R&D‐intensive firms are substantially larger than insider gains in firms without R&D. Insiders also take advantage of information on planned changes in R&D budgets. R&D is thus a major contributor to information asymmetry and insider gains, raising issues concerning management compensation, incentives, and disclosure policies.